1983
DOI: 10.1002/j.1556-6978.1983.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Self‐Observation, Self‐Modeling, and Practice Without Video Feedback for Improving Counselor Interviewing Behaviors

Abstract: This study evaluated the effects of three different feedback procedures on counselor trainees' interviewing behaviors that were judged by their supervisors as being inappropriate in a counseling session. In addition to informing each trainee in writing o f t h e specific target behavior(s) he or she was to attempt to improve, the feedback conditions consisted of either (a) self-observation of edited videotapes of appropriate-only behavior (entitled self-as-a-model), (b) self-observation of unedited videotapes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Coupled with the data reported by Hosford and Johnson (1983) that this technique is superior to self-observation in extinguishing of inappropriate interviewing behavior, the present findings suggest that Self-as-a-Model offers the opportunity for beginning trainees to experience video feedback and acquire skills in a more conducive, nonthreatening environment than that offered by self-observation.…”
Section: Self-observationsupporting
confidence: 76%
See 1 more Smart Citation
“…Coupled with the data reported by Hosford and Johnson (1983) that this technique is superior to self-observation in extinguishing of inappropriate interviewing behavior, the present findings suggest that Self-as-a-Model offers the opportunity for beginning trainees to experience video feedback and acquire skills in a more conducive, nonthreatening environment than that offered by self-observation.…”
Section: Self-observationsupporting
confidence: 76%
“…Using the technique with counselor trainees, Hosford and Johnson (1983) compared the relative effectiveness of Self-as-a-Model, self-observation, and practice with video feedback for the improvement of specific interviewing behaviors. The results of this study indicated that for all subjects, most of the inappropriate behaviors were greatly reduced.…”
Section: Effects Of Self-observation and Self-as-a-model On Counselormentioning
confidence: 99%
“…Further, the studies had to describe quantitative research and to report on the statistical data required to calculate an effect measure. A number of studies did not qualify for inclusion for this reason (Ajayi-Dopemu and Talabi 1986;Brown and Kameen 1975;Cassata and Clements 1978;Cassata et al 1977;Fyffe and Oei 1979;Gask 1998;Gask et al 1991Gask et al , 1987Hosford and Johnson 1983;Hougham 1992;Hulsman et al 2009;Kern 1980;Levinson and Roter 1993;Marita et al 1999;Napper-Owen and Phillips 1995;Schmidt and Messner 1977;Scott et al 1983;Sollie and Scott 1983;Speidel and Tharp 1978;Star 1977;Vassilas and Ho 2000;Verby et al 1979;Zick et al 2007). Finally, two studies which were written in Japanese (Endo 2008;Tomita and Tagami 1999) were not included.…”
Section: Literature Searchmentioning
confidence: 94%
“…Because of the complete lack of VSM effect on assembly time and self-efficacy dependent variables, it is difficult to add any definitive conclusions to the literature. However, the present investigation is not alone in being unable to demonstrate a VSM effect on self-efficacy (Winfrey & Weeks, 1993) and is part of a growing number of studies that demonstrate the VSM strategy to be ineffective or only equal in effect to other modeling treatments with adult subjects in general (e.g., Hosford & Brown, 1976, as cited in Meharg & Woltersdorf, 1990Hosford & Johnson, 1983;Meharg & Lipsker, 1991).…”
Section: Sdmrmentioning
confidence: 77%